The relationship between maternal–fetal attachment and maternal self-efficacy in Iranian women: a prospective study. (27th May 2018) - Delavari, Mina; Mohammad-Alizadeh-Charandabi, Sakineh; Mirghafurvand, Mojgan
Abstract: Introduction: This prospective study was conducted to determine the relationship between maternal–fetal attachment and maternal self-efficacy. Maternal self-efficacy contributes significantly to the mental health of the mother and infant. Maternal–fetal attachment facilitates maternal role attainment and might improve maternal self-efficacy. Methods: This study was conducted on 242 women. The data collection tools used included a socio-demographic and obstetric questionnaire, Cranley's Maternal–Fetal Attachment Scale, the Edinburgh Postnatal Depression Scale and the Maternal Self-Efficacy Scale. A multivariate linear regression was used to estimate the extent to which maternal–fetal attachment affects maternal self-efficacy. Results: Pearson's correlation test showed a moderate but significant positive correlation between maternal–fetal attachment and self-efficacy ( r = 0.48, P < 0.001). The highest correlation with self-efficacy was observed in the domain of 'differentiation of self from fetus' ( r = 0.43) and the lowest in the domain of 'giving of self' ( r = 0.25). According to the multivariate linear regression, the domain of 'Interaction with fetus' had a significant relationship with maternal self-efficacy (P = 0.009). Conclusion: Maternal–fetal attachment would appear to be a factor related to postpartum maternal self-efficacy which suggests identifying and supporting women with low self-efficacy may increase maternal–fetal attachment and thereby maternal self-efficacy.